Depiction of Machismo through Castillo Brothers in Oscar Hijuelos’ The Mambo Kings Play Songs of Love - Supiastutik Supiastutik; Septania Alya Rakhman; Syamsul Anam (Pusat Studi Gender Universitas Jember, 2024)
The Mambo Kings Play Songs of Love (1989) is a novel by Oscar Hijuelos, a Cuban-American writer. It talks about the lives of Cesar and Nestor Castillo, Cuban immigrants who live in America to pursue their dreams as musicians. The novel strongly connects to Latin American culture. The Castillo brothers are known for embracing their